Debit Puncak Harian Tahunan Metode HSS Nakayasu dan Debit Terukur di DAS Muke Kabupaten Timor Tengah Selatan - Monica T.R Utung; Judi K Nasjono; Elia Hunggurami (Universitas Nusa Cendana, 2021)
The Muke River is prone to flooding. flooding is caused by conversion in land use due to the migrating plantation system. In the Muke river, it is necessary to analyze the discharge estimation to determine the potential of water in the Muke river. In this study, the authors performed peak discharge calculation using measured calculation model and calculate. Measured calculations using discharge’s curve and calculated by using hydrographic method of synthetic unit namely Nakayasu. The results of the analysis for the calculation of discharge on the Muke river using the discharge curve obtained that the peak discharge occurred in 2012 with Qmax = 99.41 m3/s and the smallest discharge occurred in 2010 with Qmin = 13.19 m3/s, the results of the analysis for the calculation of discharge on the Muke river using the Nakayasu method obtained peak discharge occurred in 2010 with Qmax= 184.74 m3/s and the smallest discharge occurred in 2014 with Qmin = 94.33 m3/s.